Molecular architecture and diversity of StopGo/2A translational recoding - Xueyan Li; Philipp K. Zuber; Gary Loughran; Pramod R. Bhatt; Fatema Alquraish; V. Ramakrishnan; Andrew E. Firth; John F. Atkins (Proceedings of the National Academy of Sciences, 2026)
Viral 2A sequences trigger a cotranslational peptide bond formation “skipping” event, termed “StopGo,” to generate two separate proteins from a single open reading frame without classical termination. To investigate the mechanism of StopGo, we determined the cryo-EM structure of a mammalian ribosome positioned at the foot-and-mouth disease virus 2A (F2A) site. The structure shows how interactions between the F2A nascent chain (NC) and the ribosomal exit tunnel induce a conformational change in the peptidyl transferase center that precludes further translation elongation but instead pre-exposes the P-tRNA:F2A-NC ester bond for hydrolysis and NC release. Additionally, we bioinformatically characterized variation and host association across nearly 10,000 StopGo sequences identified in virus genomes. We expanded the canonical core motif to (D/G/C/N)(V/I)ExNPGP and identified additional rare but functional variants. We also revealed several distinct upstream motifs that we showed biochemically to be important for StopGo activity. Interestingly, although StopGo is known to be functionally active in plants, we found no evidence for natural utilization of StopGo by plant viruses. Overall, these findings provide valuable insights into a unique translation recoding mechanism, and lay foundations for further optimization of multigene expression in biotechnology.